ENHANCING MATHEMATICAL LITERACY THROUGH PROBLEM-BASED LEARNING: A MIXED-METHODS ANALYSIS OF STUDENT PERFORMANCE - Ashari, Nur Wahidin (Universitas Cokroaminoto Palopo, 2024)
This study is a descriptive research using a qualitative and quantitative approach (mixed method) aimed at analyzing the mathematical literacy skills of students in Problem-Based Learning (PBL) instruction. The subjects of this study are students who participated in the research. The research instrument is the researcher themselves. Additionally, supporting instruments used in this study include: 1) a mathematical literacy skills test, 2) an observation sheet for the implementation of Problem-Based Learning, and 3) an observation sheet for student activity during learning. The data collected were analyzed using quantitative analysis, where the researcher calculated the mean and standard deviation from the motivation and interest in learning questionnaires. Further, qualitative analysis was conducted by the researcher through data reduction, presenting the data, and drawing conclusions. The results of the study indicate that students' mathematical literacy skills in PBL instruction are excellent.